Socioeconomic Determinants of Stunting in Indonesia: The Role of Poverty, Women’s Empowerment, and Regional Economic Growth - Nindien, Qurrota Ayu; Yohanes Novi Armunanto; Nadya Ramadhani Ikhsana; Dina Arini Adipathy (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study investigates stunting in Indonesia by examining its relationship with poverty, education, and women’s empowerment across 34 provinces. Stunting remains a major global health concern because it can affect the long-term quality of human resources, while poverty and education are often viewed as socioeconomic conditions that influence household nutrition and child growth. Existing studies commonly discuss stunting from a health perspective, but this research positions poverty and women’s empowerment as important explanatory variables in understanding stunting in Indonesia. Using panel data from 34 provinces, this research applies a quantitative regression approach to analyze how poverty, the Female Human Development Index, women’s average years of schooling, and GRDP per capita growth are associated with stunting prevalence. The findings indicate that poverty has a positive and statistically significant relationship with stunting. The findings indicate that poverty has a positive and statistically significant relationship with stunting. The main contribution of this study is its focus on women’s empowerment as an important socioeconomic factor in reducing stunting.